2012
DOI: 10.5812/hepatmon.6050
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Knowledge About Hepatitis C Infection Rates Among Patients With Inherited Coagulation Disorders in Countries Under the Eastern Mediterranean Region Office of WHO (EMRO): A Meta-Analysis

Abstract: Context: Hepatitis C virus (HCV) infection is a public health problem. HCV alone is responsible for 90% cases of acute hepatitis among multiply transfused patients who are at risk of cirrhosis and hepatocellular carcinoma (HCC). Objectives: To provide a clear picture of available data, we performed a systematic review of the epidemiological characteristics of HCV infection among patients with inherited coagulation disorders in the countries under the Eastern Mediterranean Region Office (EMRO). Evidence Acquisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…Hepatitis C antibody positivity, in this Brazilian cohort of patients with haemophilia, was significantly higher than that estimated by the World Health Organization for the general population in Latin America (35.8% vs 0.7%, respectively) . However, this result is slightly lower than that found in other populations with haemophilia worldwide, as recently described in the United States (32.6%‐92.3%), Western and Central Europe (55.8%), Taiwan (54.3%), Middle West countries (48.3%) and Australia (52.0%) …”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Hepatitis C antibody positivity, in this Brazilian cohort of patients with haemophilia, was significantly higher than that estimated by the World Health Organization for the general population in Latin America (35.8% vs 0.7%, respectively) . However, this result is slightly lower than that found in other populations with haemophilia worldwide, as recently described in the United States (32.6%‐92.3%), Western and Central Europe (55.8%), Taiwan (54.3%), Middle West countries (48.3%) and Australia (52.0%) …”
Section: Discussioncontrasting
confidence: 62%
“…Nevertheless, the high HCV prevalence among patients with haemophilia around the world persists until now . A Brazilian national report supported by data collected from 2005 to 2007 showed that 34.9% and 29.7% of Brazilian patients with haemophilia A and B, respectively, were hepatitis C antibody (anti‐HCV)‐positive .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of effective blood and blood product screening before 1990, many patients with HBD were infected with the hepatitis C virus (HCV) [1]. A metaanalysis showed that 48% of Iranian hemophilic patients were infected with HCV that also varies 24-89% in different countries of the world [1,2]. About 75-85% of patients who contracted HCV will develop chronic hepatitis C (CHC), which is associated with the increased risk of cirrhosis, end-stage liver diseases, and hepatocellular carcinoma [3].…”
Section: Introductionmentioning
confidence: 99%
“…Treated or recombinant clotting factors are now utilized routinely, and new cases of HCV infection in patients with congenital bleeding disorders are uncommon . The prevalence of hepatitis C among hemophilic patients varies from 24% to 95% throughout the world . Prior to the introduction of efficacious HCV direct‐acting antiviral agents (DAAs) in 2011, A 24‐48 week course of Pegylated‐Interferon‐α‐2a (PegIFN‐α‐2a) or PegIFN‐α‐2b combined with Ribavirin (RBV; PegIFN/RBV) was the recommended treatment for CHC .…”
Section: Introductionmentioning
confidence: 99%